Практический курс английского языка для устного перевода (English course for interpreters) электронный курс - Квашнина, О. С. лингвист старший преподаватель Томского политехнического университета 1980- (TPU Moodle, 2021)
The course is intended for students who are aquiring an additional specialization of Translators in professional sphere of communication. The main objective of the course is to develop students' English language competency (listening, reading, speaking, writing) at the level that will enable them to function adequately as interpreters (English-Russian) and to develop the basic interpreting skills. The course covers 2 semesters of the first academic year and is supplemented by a Grammar course. The course covers such topics as memory as a fundamental human capacity, threats of artificial intelligence, longevity, biomimicry, photography, nuclear engineering, biotechnologies, etc. Special attention is paid to the development of students' listening skills and memory capacity as one of the crucial skills for interpreting.